Fracture Resistance of Pressed and Milled Lithium Disilicate Anterior Complete Coverage Restorations Following Endodontic Access Preparation. Issue 2 (22nd April 2018) - Gerogianni, Petrina; Lien, Wen; Bompolaki, Despoina; Verrett, Ronald; Haney, Stephan; Mattie, Patrick; Johnson, Russell
Abstract: Purpose: This in vitro study evaluated the fracture resistance and clinical prognosis of anterior lithium disilicate crowns (e.max Press and e.max CAD), following endodontic access and repair. The research design simulates intraoral loading conditions to produce clinically applicable results. Materials and Methods: Monolithic anterior crowns, based on #8 anatomy, were fabricated from e.max Press ingots and e.max CAD blocks and adhesively bonded on identical dies milled out of a dentin analog material (NEMA G10). Specimens were divided into 4 groups: intact pressed, repaired pressed, intact milled, and repaired milled (n = 15/group). Repaired pressed and repaired milled were prepared with a standardized endodontic access and repaired using a porcelain repair system and composite resin. All crowns were cyclically loaded under simulated oral conditions and then loaded to failure in water, using a universal testing machine. Data were interpreted using ANOVA/Tukey post‐hoc test (α = 0.05). Results: Mean loads to failure ranged from 758.9 to 931.4 N for the 4 groups, indicating that both fabrication techniques, pressed and milled, yielded restorations that could reasonably withstand maximum masticatory forces. The pressed groups (923.7 N) exhibited significantly higher fracture resistance than the milled groups (797.5 N), p = 0.0002. When milled and pressed groups were categorized into intact and repaired subgroups, no difference was found in fracture resistance between the subgroups. Differences were noted in the modes of fracture, where the milled groups (intact and repaired) exhibited higher frequency of catastrophic fractures than the pressed groups. Conclusions: Endodontic access preparation does not appear to affect fracture resistance of an anterior lithium disilicate restoration, suggesting that replacement may not be necessary. Fabrication technique had a significant effect on fracture resistance and fracture mode of lithium disilicate restorations. The pressed fabrication technique resulted in significantly greater crown strength and fracture resistance than the milled technique.